Developing Learning Outcome Indicators in Akidah Akhlak Education: A Case Study in Islamic Junior Secondary Schools under the Merdeka Curriculum - Rifdaa Aulia; Irawan; Ishma Shafiyatu Sa’diyah; Mohammad Husni Mubarok (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2026)
This study aims to analyze the development of learning outcome indicators in the instructional planning of Akidah Akhlak for seventh-grade students in Phase D under the Merdeka Curriculum. The main issue lies in non-operational indicators, particularly in the affective domain, which limits effective assessment and character development. This study employed a qualitative case study design conducted at MTsN 01 Kota Bekasi, Indonesia. Data were collected through document analysis, observations, and interviews with a teacher. The analysis focused on the alignment between indicators, learning outcomes, student characteristics, and assessment practices. The results show that cognitive indicators are clearly formulated and measurable. However, affective indicators remain general, lack observable behavioral criteria, and are not integrated into assessment practices. These findings highlight the importance of developing operational and measurable affective indicators to support holistic learning. The study implies that teachers need greater support in designing indicator-based assessment frameworks and strengthening affective indicator formulation to ensure that character development objectives within Akidah Akhlak education can be assessed systematically and effectively under the Merdeka Curriculum.